Emissões de gases fluorados causadores de efeitoestufa: desenvolvimento e análise de cenários para o Brasil até 2050 - Hebeda, Otto (2017)
Fluorinated gases are fluids with high global warming potential. Although, presently less than 2% a year, the total global emissions of these compounds have been growing sharply in the last years. This study aims to elaborate scenarios for fluorinated greenhouse gas (HFC, PFC and SF6) emissions in Brazil up to 2050, and to evaluate potentials and costs of implementing different mitigation options. For the scenario considering the highest economic growth, it is estimated that, in 2050, the emissions of fluorinated gases will be more than 12 times higher than the value observed in 2015, reaching a total of 111,569 GgCO2eq. In general, air conditioning equipments that presented the greatest contribution to the total emissions between 2015 and 2050 (84%). The implementation of abatement measures is capable of reducing up to 95% of total emissions in this period. In 2050, at negative costs, it is possible to cut 37% of all emissions, and cost lower than 20 M€/GgCO2eq, it is possible to cut 97% of all emissions.